2011
DOI: 10.1007/bf01617389
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic and diastolic functions in patients with sickle cell anemia

Abstract: The aim of this study was to evaluate the left ventricular systolic and diastolic functions in patients with sickle cell anemia. Fifty-four patients (34 male, 20 female, mean age 22.6 +/- 7.3 years) and 23 healthy persons (12 male, 11 female, mean age 26.7 +/- 6.8 years) were studied. After clinical examination and routine biochemical evaluation by a hematologist, patients with sickle cell anemia were admitted to the study. M-mode and 2-dimensional and Doppler echocardiographic measurements of patients and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Cardiac alterations in SCD have been previously studied. In agreement with published literature, we found in our SCD patients a preserved LV ejection fraction 5,19,8,11,13 along with LV dilation [5][6][7]4,8,10,11,13 and an increase in LV mass [5][6][7]14,4,8,10,11,13 . Such LV enlargement has been hypothesized to reflect a remodeling mechanism to adapt to the elevation in stroke volume induced by the chronic anemia-related decrease in blood oxygenation in such disease to match metabolic demand 29 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cardiac alterations in SCD have been previously studied. In agreement with published literature, we found in our SCD patients a preserved LV ejection fraction 5,19,8,11,13 along with LV dilation [5][6][7]4,8,10,11,13 and an increase in LV mass [5][6][7]14,4,8,10,11,13 . Such LV enlargement has been hypothesized to reflect a remodeling mechanism to adapt to the elevation in stroke volume induced by the chronic anemia-related decrease in blood oxygenation in such disease to match metabolic demand 29 .…”
Section: Discussionsupporting
confidence: 92%
“…Left ventricular (LV) alterations in SCD have been widely described, including LV dilation [4][5][6][7][8][9][10][11][12][13] , an increase in LV mass 5,7,14,4,8,[10][11][12][13] , as well as diastolic dysfunction 7,11,13,15 . Today, up to 25% of SCD deaths are related to cardiovascular causes 16 and diastolic dysfunction is a known independent risk factor for mortality in SCD patients 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in SCD children with no history of overt stroke or seizures, we have reported that higher systolic blood pressure (SBP) is associated with increased risk of an silent cerebral infarction (SCI) [13], a common form of neurological injury among children with SCD, occurring in at least 27% prior to six years of life and 37% by 14 years of life [14,15]. In addition, previous clinical studies have shown that the SCD may have a deleterious effect on myocardium, which contributes to abnormal rates of change in left ventricular cavity size and systolic/diastolic function in SCD patients [16-18]. Indeed, nearly one third of adults with SCD also develop an elevated tricuspid regurgitant velocity (TRV) that is associated with a much higher death rate in SCD patients compared to patients with SCD without elevated TRV.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular causes account for nearly one‐fourth of all premature deaths in adults with sickle cell anemia (SCA) 1–3 . The maladaptive cardiac remodeling seen in SCA underlies the cardio‐pathology of SCA and worsens with age 4–7 . Moderate–severe anemia from the ongoing hemolysis results in a compensatory hemodynamic state comprising increased cardiac output, pan‐chamber dilation, and left ventricular (LV) hypertrophy, seen in both children and adults with SCA 8–11 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The maladaptive cardiac remodeling seen in SCA underlies the cardio-pathology of SCA and worsens with age. [4][5][6][7] Moderate-severe anemia from the ongoing hemolysis results in a compensatory hemodynamic state comprising increased cardiac output, pan-chamber dilation, and left ventricular (LV) hypertrophy, seen in both children and adults with SCA. [8][9][10][11] LV systolic dysfunction is a rare complication in adults.…”
mentioning
confidence: 99%